Project Report Accident Avoidance System and Location Based Vehicle Control - POOJITH SSHETTY,SHASHI KUMAR V K,SHRIGANESH UDANESHWAR AR BHAT, and SURENDRA KUMAR G P. (2013)
INTERNAL GUIDE : KAVITHA D. EXTERNAL GUIDE:KRISHNAMURTHY M. USN NO : 1MJ10EC065,1MJ10EC088,1MJ10EC100. CARRIED OUT AT : MVJ College Of Engineering Bangalore-67 ACC N : PR2118
Keywords: Accident Avoidance System and Location Based Vehicle Control